RRT and Octomap based 3D environment exploration and mapping - Koirala, Koshish (2020)
A Master of Science thesis in Mechatronics Engineering by Koshish Koirala entitled, “RRT and Octomap Based 3D Environment Exploration and Mapping”, submitted in May 2020. Thesis advisor is Dr. Shayok Mukhopadhyay. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).